Blood flow restriction resistance training: Potential benefits of choking the muscles - Koziris, L. (Strength and Conditioning Journal, 2014)
Blood flow restriction can be used in resistance exercise to augment physiological challenges and stimulate adaptations when heavy loads are contraindicated. Female athletes using only 20% 1 repetition maximum substantially improved their muscular endurance, strength, hypertrophy, and motoneuron recruitment efficiency, when training was coupled with local occlusion or even with breathing hypoxic air.